The Impact of Endometritis on Specific Oxidative Stress Parameters in Cows - KAYA, S.; ÖĞÜN, M.; ÖZEN, H.; KURU, M.; ŞAHIN, L.; KÜKÜRT, A.; KAÇAR, C. (Journal of the Hellenic Veterinary Medical Society, 2018)
This study was aimed to investigate the presence of uterine infection and the relationship between the severity of uterine infection and some oxidative stress parameters in cows in early postpartum period. Sixty six cows that were in the period between the 30th and 32rd days of postpartum were included in the study. Endometrial inflammation was scored according to the condition of the uterus at rectal and ultrasonographic examinations and the character and amount of uterine discharge from endometritis I through III, the latest being the most severe. Endometrial samples were taken from the clinically healthy animals by cytobrush method, and then stained with Giemsa for presence of polymorphonuclear leukocytes (PMN). Cows with a PMN percentage less than 18% were considered to be healthy (control, n=20). All cows were sampled for blood. Nitric oxide (NO) levels in Group I (Endometritis I; n=20), Group II (Endometritis II; n=16), Group III (Endometritis III; n=10) and the control group were determined to be 23.0±0.63 nmol/mL, 32.23±0.97 nmol/mL, 36.56±0.48 nmol/mL, and 11.10±0.29 nmol/mL, respectively. The differences among the groups were found to be statistically significant. Malondialdehyde (MDA) level was highest in Group III (6.38±0.13 μmol/L), and its level significantly decreased with the reduced severity of endometritis. The comparison of the groups for total antioxidant capacity (TAC) and total oxidant capacity (TOC) demonstrated that endometritis caused a decrease in TAC levels (P<0.05), but did not affect TOC levels. Endometritis increased serum NO and MDA levels, and decreased TAC levels, but had no effect on TOC levels. In conclusion, NO and MDA, as well as TAC can be used as a biochemical marker for estimation of the severity of endometritis in cows.